2016
DOI: 10.1002/jmv.24462
|View full text |Cite
|
Sign up to set email alerts
|

Overt and occult hepatitis B virus infection among treatment‐naïve HIV‐infected patients in Brazil

Abstract: Although hepatitis B virus (HBV) and human immunodeficiency virus (HIV) co-infection is common, only few data are available on HBV among HIV patients including occult hepatitis B infection (OBI), regardless of serological markers. This study aims to determine the prevalence of OBI and overall HBV infection, associated factors, HBV genotypes, and surface (S) gene mutations in a population of treatment-naïve HIV-infected patients in Brazil. A cross-sectional study was conducted in treatment-naïve HIV-infected pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
0
6
0
5
Order By: Relevance
“…Instead, some other “a” determinant mutations were found. Previous investigations had shown P127T, Y134I, E164D, I195M, P120S [Taffon et al, ], Y100C, T131N, and D144A mutations [Oliveira et al, ] in OBI‐HIV coinfection. Moreover, in the present study, other unreported new mutations among these OBI‐HIV‐1‐positive patients were found.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, some other “a” determinant mutations were found. Previous investigations had shown P127T, Y134I, E164D, I195M, P120S [Taffon et al, ], Y100C, T131N, and D144A mutations [Oliveira et al, ] in OBI‐HIV coinfection. Moreover, in the present study, other unreported new mutations among these OBI‐HIV‐1‐positive patients were found.…”
Section: Discussionmentioning
confidence: 99%
“…Tengan et al [15] reported HBsAg prevalence in HIV of 3.3% in [20,21]. HBV genotype A was the most detected in studies from Brazil and Argentina while genotype F was most found in Colombia [17,[19][20][21][22].…”
Section: Hepatitis B and C Prevalence In Patients Infected By Hivmentioning
confidence: 99%
“…In Brazil, HBsAg prevalence in HIV infected individuals ranges from 1.9 to 10.3% according geographical regions [15][16][17][18]. Tengan et al [15] reported HBsAg prevalence in HIV of 3.3% in [20,21]. HBV genotype A was the most detected in studies from Brazil and Argentina while genotype F was most found in Colombia [17,[19][20][21][22].…”
Section: Hepatitis B and C Prevalence In Patients Infected By Hivmentioning
confidence: 99%
“…HBV activation could be associated with severe hepatitis and liver failure (6)(7)(8)(9)(10)(11)(12)(13). There are conflicting data whether HBV replication may be inhibited by coinfection with other agents, especially HCV or HIV (14)(15)(16)(17)(18)(19)(20). Although HBV replication is commonly inhibited in the presence of HCV coinfection, a total HBV activation rate of 14.5% is reported following interferon (IFN)-induced HCV eradication (21) .Thus, the individuals with active HBV and HCV infections likely show a high HCV viral load, and low or undetectable HBV DNA levels.…”
Section: Introductionmentioning
confidence: 99%